The Ragwitch - Nix, Garth (New York : Eos, 2004)
When his sister Julia falls under the spell of the evil Ragwitch and her minions, Paul must journey across time to a distant dimension and rally the forces of good to rescue Julia and save the magical kingdom of Yendre.
1020
Accelerated Reader AR
Keywords: Fantasy